2021
DOI: 10.1002/jctb.6853
|View full text |Cite
|
Sign up to set email alerts
|

Transient shifts in hydraulic retention times improve the methane production from ruminal hydrolysates of agave bagasse

Abstract: BACKGROUND Valorization of lignocellulosic wastes such as agave bagasse from tequila industries can be enhanced using efficient biomass pretreatments. However, the next challenge requires finding the best process conditions to produce methane and remove chemical oxygen demand (COD) from the pretreatment hydrolysates. In this work, an innovative feeding strategy based on alternating hydraulic retention times (HRT) was investigated to improve methane production from ruminal hydrolysates of Agave tequilana bagass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Regarding Biofuel Production , six articles mainly focused on the production of methane and hydrogen from a variety of waste streams were included. Vital‐Jácome et al 18 . reported that transient shifts of hydraulic retention time improve the methane production in UASB reactors using ruminal hydrolysates of agave bagasse as substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Biofuel Production , six articles mainly focused on the production of methane and hydrogen from a variety of waste streams were included. Vital‐Jácome et al 18 . reported that transient shifts of hydraulic retention time improve the methane production in UASB reactors using ruminal hydrolysates of agave bagasse as substrate.…”
mentioning
confidence: 99%
“…Regarding Biofuel Production, six articles mainly focused on the production of methane and hydrogen from a variety of waste streams were included. Vital-Jácome et al 18 reported that transient shifts of hydraulic retention time improve the methane production in UASB reactors using ruminal hydrolysates of agave bagasse as substrate. In Mexico, valorization of residues from tequila industry is a central objective of local authorities and this work showed the potential of these residues for generating renewable energy.…”
mentioning
confidence: 99%